PENGARUH PENERAPAN ROUTING I-BGP TERHADAP WAKTU FAILOVER DALAM JARINGAN LOKAL - Hartanto, Agus; Surono, Surono; Wicaksana, Dinar Anggit (Jurnal Transformatika, 2025)
The reliability of computer networks is a crucial element in supporting various sectors in the digital era. Failover, an automatic switching mechanism to a backup route when the main route fails, heavily depends on response speed and the capability of routing protocols. This study evaluates the effectiveness of Internal Border Gateway Protocol (I-BGP) in accelerating failover time on a local network based on Mikrotik connected via VPN. The performance of I-BGP is compared with OSPF, RIP, and Static Routing through tests on failover time, packet loss, and bandwidth efficiency. The results show that I-BGP has the fastest failover time (0.51 seconds), minimal packet loss (2 packets), and the highest bandwidth utilization (95%). ANOVA testing confirms significant differences among the protocols (F=776.898, p<0.001). These findings highlight the superiority of I-BGP as an optimal solution for fast and reliable failover. In the future, as network complexity and challenges increase, comprehensive studies and further research on connectivity disruptions related to security factors and AI-based solutions will be necessary